Case Report: Leaflet thrombosis after transcatheter valve-in-valve aortic valve replacement in prosthetic valve endocarditis - Zhou, Yuhan; Fu, Bo; Jiang, Nan; Guo, Zhigang (Frontiers in Cardiovascular Medicine, 2025)
A 70-year-old female patient with a history of bioprosthetic aortic valve replacement and coronary artery bypass graft presented with bioprosthetic valve failure secondary to prosthetic valve endocarditis. The patient was deemed unsuitable for surgery by the heart team, following which she underwent transcatheter aortic valve-in-valve replacement. This resulted in early death due to myocardial infarction and acute heart failure. A computed tomography revealed subclinical leaflet thrombosis. This case highlights the importance of postoperative anticoagulation therapy.